Efektivitas Teknik Perawatan Luka Modern pada Pasien Ulkus Diabetikum - Sarwoto, Sarwoto; Fitria, Reni; Putri, Dian Eka (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2025)
Diabetic ulcers are one of the chronic complications of diabetes mellitus that can lead to amputation if not treated properly. Modern wound care techniques have been widely used as a more effective approach to accelerate wound healing. Morbidity after ulceration is high, with a recurrence rate of 65% at 3–5 years, a lifetime incidence of lower extremity amputation of 20%, and a 5-year mortality rate of 50–70%.The purpose of this study was to analyze the effectiveness of modern wound care techniques in diabetic ulcer patients in modern wound care practices. The study design used a pre-experimental study with a one group pre-post test design, with a population of 34 respondents, using purposive sampling. Bivariate analysis was performed using the Wilcoxon test. Of the 34 respondents, before (Pre-Test) 23 (67.6%) respondents were in stage 3 of diabetic ulcers and after (Post-Test) 22 (64.7%) respondents were in stage 2. The statistical test results using the Wilcokson test obtained a p-value of 0.000 (<0.05), so it was concluded that there was an effect of modern wound care techniques on the healing of diabetic ulcer in modern wound care practices in Giri Purno Village, Tebo Regency, Jambi in 2024. Primary health centers are expected to develop modern wound care services, provide training for health workers, and educate the community on the prevention of diabetic ulcers.